Therapeutic potential of green tea catechin, (-)-epigallocatechin-3-O-gallate (EGCG) in SARS-CoV-2 infection: Major interactions with host/virus proteases - Biswanath Dinda; Subhajit Dinda; Manikarna Dinda (Elsevier, 2023)
Background: The current COVID-19 pandemic from the human pathogenic virus SARS-CoV-2 has resulted in a major health hazard globally. The morbidity and transmission modality of this disease are severe and uncontrollable. As no effective clinical drugs are available for treatment of COVID-19 infection till to date and only vaccination is used as prophylaxis and its efficacy is restricted due to emergent of new variants of SARS-CoV-2, there is an urgent need for effective drugs for its treatment. Purpose: The aim of this review was to provide a detailed analysis of anti-SARS-CoV-2 efficacy of (-)-epigallocatechin-3-O-gallate (EGCG), a major catechin constituent of green tea (Camellia sinensis (L.) Kuntze) beverage to highlight the scope of EGCG in clinical medicine as both prophylaxis and treatment of present COVID-19 infection. In addition, the factors related to poor oral bioavailabilty of EGCG was also analysed for a suggestion for future research in this direction. Study design: We collected the published articles related to anti-SARS-CoV-2 activity of EGCG against the original strain (Wuhan type) and its newly emerged variants of SARS-CoV-2 virus. Methods: A systematic search on the published literature was conducted in various databases including Google Scholar, PubMed, Science Direct and Scopus to collect the relevant literature. Results: The findings of this search demonstrate that EGCG shows potent antiviral activity against SARS-CoV-2 virus by preventing viral entry and replication in host cells in vitro models. The studies on the molecular mechanisms of EGCG in inhibition of SARS-CoV-2 infection in host cells reveal that EGCG blocks the entry of the virus particles by interaction with the receptor binding domain (RBD) of viral spike (S) protein to host cell surface receptor protease angiotensin-converting enzyme 2 (ACE2) as well as suppression of the expressions of host proteases, ACE2, TMPRSS2 and GRP78, required for viral entry, by Nrf2 activation in host cells. Moreover, EGCG inhibits the activities of SARS-CoV-2 main protease (Mpro), papain-like protease (PLpro), endoribonuclease Nsp15 in vitro models and of RNA-dependent RNA polymerase (RdRp) in molecular docking model for suppression of viral replication. In addition, EGCG significantly inhibits viral inflammatory cytokine production by stimulating Nrf2- dependent host immune response in virus-infected cells. EGCG significantly reduces the elevated levels of HMGB1, a biomarker of sepsis, lung fibrosis and thrombotic complications in viral infections. EGCG potentially inhibits the infection of original (Wuhan type) strain of SARS-CoV-2 and other newly emerged variants as well as the infections of SARS-CoV-2 virus spike-protein of WT and its mutants-mediated pseudotyped viruses . EGCG shows maximum inhibitory effect against SARS-CoV-2 infection when the host cells are pre-incubated with the drug prior to viral infection. A sorbitol/lecithin-based throat spray containing concentrated green tea extract rich in EGCG content significantly reduces SARS-CoV-2 infectivity in oral mucosa. Several factors including degradation in gastrointestinal environment, low absorption in small intestine and extensive metabolism of EGCG are responsible for its poor bioavailability in humans. Pharmacokinetic and metabolism studies of EGCG in humans reveal poor bioavailability of EGCG in human plasma and EGCG-4"-sulfate is its major metabolite. The concentration of EGCG-4"-sulfate in human plasma is almost equivalent to that of free EGCG (Cmax 177.9 vs 233.5 nmol/L). These findings suggest that inhibition of sulfation of EGCG is a crucial factor for improvement of its bioavailability. In vitro study on the mechanism of EGCG sulfonation indicates that sulfotransferases, SULT1A1 and SULT1A3 are responsible for sulfonation in human liver and small intestine, respectively. Some attempts including structural modifications, and nanoformulations of EGCG and addition of nutrients with EGCG have been made to improve the bioavailability of EGCG. Conclusions: The findings of this study suggest that EGCG has strong antiviral activity against SARS-CoV-2 infection independent of viral strains (Wuhan type (WT), other variants) by inhibition of viral entry and replication in host cells in vitro models. EGCG may be useful in reduction of this viral load in salivary glands of COVID-19 patients, if it is applied in mouth and throat wash formulations in optimal concentrations. EGCG could be a promising candidate in the development of effective vaccine for prevention of the infections of newly emergent strains of SARS-CoV-2 virus. EGCG might be useful also as a clinical medicine for treatment of COVID-19 patients if its bioavailability in human plasma is enhanced.